Analisis Proses Berpikir Matematis Siswa dalam Menyelesaikan Soal HOTS Berdasarkan Teori Alan H. Schoenfeld di Kelas V SD - Sofyan Revydo Saputra; Pandu Fathan Albany; Ardyan Putra Mahendra; Bimma Aryan Cendy Putra; Rissa Prima Kurniawati (Universitas PGRI Madiun, 2026)
This study aims to describe the mathematical thinking processes of fifth-grade elementary school students in solving Higher Order Thinking Skills (HOTS) problems based on Alan H. Schoenfeld's theory. A descriptive qualitative method was employed involving 4 student subjects selected through purposive sampling. Data were collected via written tests using Least Common Multiple (LCM) word problems alongside documentation. The data analysis utilized Schoenfeld's five problem-solving stages: reading, analysis, exploration, implementation, and verification. The results indicate that students effectively and systematically navigated all five stages. Generally, the students successfully identified the main problem information, linked it to the LCM concept, selected the prime factorization strategy, performed accurate procedural calculations, and verified the accuracy of their final answers. These findings demonstrate that Schoenfeld's framework is highly effective for mapping how elementary students apply higher-order reasoning to solve contextual, non-routine mathematical problems.